President-making in the Gilded Age the nominating conventions of 1876-1900 - Haynes, Stan M. 1957- (McFarland & Company, Inc., Publishers, 2016)
"Nominating conventions were the highlight of presidential elections in the Gilded Age, an era when there were no primaries, no debates and nominees did little active campaigning. Unlike modern conventions, the outcomes were not so seemingly pre-determined. Historians consider the late 19th century an era of political corruption, when party bosses controlled the conventions and chose nominees"...